Implementasi Program Literasi Madrasah Ibtidaiyah Nahdlatul Ulama Balikpapan Tahun Ajaran 2023/2024 - Rahman, Achmad Shoufi; Baihaqi, Mohammad (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
In answering the fourth industrial revolution era, basic Islamic education institutions did not adequately apply old literacy (reading, writing, arithmetic), but had to apply new literacy (data literacy, technology literacy and human resource literacy or humanism). This article discusses the challenges and opportunities of basic Islamic education in the era of the fourth industrial revolution. Strengthening new literacy in Islamic elementary education teachers as a key to change, revitalizing literacy-based curriculum and strengthening the role of teachers who have digital competencies. The teacher plays a role in building competency generation, character, having new literacy skills, and high-level thinking skills. Islamic elementary education as a basis for determining intellectual, spiritual, and emotional intelligence in children must strengthen 21st century literacy skills. Start creative aspects, critical thinking, communicative, and collaborative. Islamic elementary education is urgently needed to strengthen new literacy and revitalize digital-based curriculum. Curriculum revitalization refers to five basic values of good students, namely resilience, adaptability, integrity, competence, and continuous improvement. Islamic elementary education educators must be digital teachers, understand computers, and be free from academic illness. The goal is to realize high competency generation, character and literacy to answer the challenges of the fourth industrial revolution era